Exploring challenges in learning grammar during Covid-19 era - Soukotta, Ruben Otniel Cristian (Universitas Kapuas, 2023)
This study aimed to explore challenges in learning grammar in an Intermediate Grammar class during COVID-19 era. The participants were English as a Foreign Language students from 2019 until 2021 who failed in Intermediate Grammar class or received C-E as the final score of this class during COVID-19. Close-ended questionnaire and interview were used as the instruments to collect the data in May and June 2022. The questionnaire asked the participants to choose responses to the statements. In the interview, the researcher involved six participants from the survey to clarify and dig in their responses using the same questions on the questionnaire. The results of this study would seem to indicate that the students failed in learning grammar class during the COVID-19 era because the grammar materials were too difficult to understand, loud noises made them unable to study peacefully when joining the online class from home. Their online grammar class was boring, and students experienced a bad internet connection. In addition, teachers and friends seemed to take an essential role in enhancing students’ grammar. At the end, this study proposed some explicit learning strategies to improve learners’ learning in an online grammar class.